Analisis struktur dan menentukan profit margin rantai pasok pemasaran kopi (studi kasus di Indonesia) - Imelda Yunita; Rika Ampuh Hadiguna (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
The role of the players in the supply chain is very significant in delivering products to consumers. As producers, the role of coffee farmers is equally crucial in improving the efficiency of the supply chain. The structure of the coffee supply chain in the research area starts with farmers, wholesalers, and consumers (exporters). The purpose of this study is to examine the structure of the coffee bean marketing chain considering the position of farmers in increasing profit margins. The focus of this research is on robusta coffee, grown in the Jambi Province as one of the coffee producers in Indonesia. The research phases analyze the structure of the supply chain and formulate a mathematical model to see the profit margins obtained by each actor in the supply chain. The results of the profit margin analysis show that farmers can make stable profits if they maintain good partnerships and thus can maintain the quality of production by consumer demand.